New species, new synonymy, taxonomic notes and new records of bark and ambrosia beetles from the southwestern United States and northern Mexico (Coleoptera: Curculionidae: Platypodinae and Scolytinae) - Atkinson, Thomas H. (Zootaxa, 2024)
Chaetophloeus flourensiae new species, is described from the Chihuahuan Desert from Arizona and western Texas and Hylocurus incognitus new species is described from Texas, Oklahoma and Louisiana. New synonymies include: Chramesus mimosae Blackman, 1938 (= Chramesus varius Wood, 1969); Hylocurus rudis (LeConte, 1876) (= Hylocurus binodatus Wood, 1974; Hypothenemus seriatus (Eichhoff, 1872) (= Stephanoderes multidentatus Hopkins, 1915, Stephanoderes nitidifrons Hopkins, 1915, Hypothenemus hopkinsi Browne, 1963); Hypothenemus pubescens Hopkins, 1915 (= Hypothenemus sparsus Hopkins, 1915, Hypothenenus similis Hopkins, 1915, Stephanoderes tridentatus Hopkins, 1915); Phloeotribus scabricollis Hopkins, 1916 (=Phloeotribus pseudoscabricollis Atkinson, 1989; Pseudothysanoes yuccae (Wood, 1956), (=Pseudothysanoes yuccavorus Wood, 1971); and Thysanoes texanus Blackman, 1943 (=Thysanoes mexicanus Wood, 1956). Hylocurus schwarzi Blackman, 1928, is redescribed including the first description of the female. New locality and host records that significantly extend the respective ranges are included for 30 species from the border region of the United States and Mexico.